Magnetic field dependence of the precursor diamagnetism in La superconductors with magnetic Pr impurities. (7th May 2015) - Soto, F; Carballeira, C; Doval, J M; Mosqueira, J; Ramallo, M V; Ramos-Álvarez, A; Sóñora, D; Verde, J C; Vidal, F
Abstract: The interplay between fluctuating Cooper pairs and magnetic impurities in conventional BCS low- T c superconductors has been studied through measurements of the magnetic field dependence of the fluctuation diamagnetism (FD) above T c in lanthanum with praseodymium impurities. These measurements provide a crucial confirmation of our previous observation (F Soto et al 2006 Europhys. Lett. 73 587 ) that in the dilute impurity regime the FD increases almost linearly with the concentration of magnetic impurities. This striking effect is attributed to a variation due to the presence of the fluctuating Cooper pairs of the coupling between magnetic impurities. To describe these results at a phenomenological level, we propose a Gaussian Ginzburg–Landau model for the FD which includes an indirect contribution proportional to both the concentration of impurities and the density of the Cooper pairs. Our approach is able to explain simultaneously the FD increase due to magnetic impurities and its decrease with the application of large magnetic fields.